2007
DOI: 10.1111/j.1469-8749.2006.tb01314.x
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation of the hips in children with bilateral spastic cerebral palsy, 1985-2000

Abstract: The aim of this study was to assess the rate of hip dislocation at different ages in children with bilateral spastic cerebral palsy attending special schools in southern Derbyshire, UK, between 1985 and 2000. The medical notes of 110 individuals (68 males, 42 females) were obtained. They were divided into four groups according to the Gross Motor Function Classification System (GMFCS). We determined whether or not their hips were dislocated at the ages of 5, 10, and 15 years, and the kind of surgery performed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…found 11% of their surveillance population had a migration percentage greater than 30% by 2 years of age. Other studies also supported the need for surveillance at a young age . Cases of displacement occurring from 8 months of age have been reported, as has dislocation before 2 years of age .…”
Section: Resultsmentioning
confidence: 75%
“…found 11% of their surveillance population had a migration percentage greater than 30% by 2 years of age. Other studies also supported the need for surveillance at a young age . Cases of displacement occurring from 8 months of age have been reported, as has dislocation before 2 years of age .…”
Section: Resultsmentioning
confidence: 75%
“…16 A variety of disease measures deteriorate over time in children with spastic CP: ambulatory ability tends to diminish, 17 stride frequency decreases, 18 and the proportion of children requiring orthopaedic surgery increases. 19,20 Our study provides evidence supporting long-term treatment with BoNT-A for lower-limb spasticity in children with CP. Lack of deterioration in MPAD over time also suggests that fewer children will require surgical intervention.…”
Section: Discussionmentioning
confidence: 71%
“…The main challenge of this follow-up programme is the early identification of children with CP and the maintenance of the database. As hip dislocation most often occurs between three and six years of age [ 9 , 34 ], all children under four years with any symptoms or signs of possible future CP should be included in the follow-up. This study showed that more than one third of the children with CP, included in the inventory for the first time, had not yet been offered participation in the CPUP programme.…”
Section: Discussionmentioning
confidence: 99%